TRIM5α/Cyclophilin A-Modified MDBK Cells for Lentiviral-Based Gene Editing - Lijing Wo; Shuhui Qi; Yongqi Guo; Chao Sun; Xin Yin (Viruses, 2025)
The human immunodeficiency virus 1 (HIV-1)-based lentivirus has been widely used for genetic modification. However, the efficiency of lentiviral-based gene modification in Madin–Darby bovine kidney (MDBK) cells is considerably limited. In this study, we have shown that siRNA-mediated depletion of TRIM5α, a restriction factor in HIV-1 infection, can dramatically enhance HIV-1 infection in MDBK cells. Furthermore, we generated a doxycycline-inducible Cas9-overexpressing MDBK cell line (MDBK-iCas9) suitable for CRISPR/Cas9-mediated editing. On this basis, we created a TRIM5α knock-out MDBK-iCas9 cell line MDBK-iCas9TRIM5α−/− without additional genome insertions by combining sgRNA transfection and single-cell cloning. We found that MDBK-iCas9TRIM5α−/− displayed greater permissiveness to lentivirus infection compared with MDBK-WT cells. Notably, we found that treatment with the chemical compound cyclosporine A, which directly interacts with cell factor cyclophilin A (CypA), could markedly increase the infectivity of lentivirus in both MDBK-iCas9TRIM5α−/− and MDBK-WT cell lines, suggesting that CypA functions independently with TRIM5α as an inhibitor of the lentivirus in bovine cells. Therefore, combining bovine TRIM5α and CypA targeting could remarkably enhance lentivirus infection. In conclusion, our findings highlight a promising gene engineering strategy for bovine cells that can surmount the significant barriers to investigating the interplay between bovine viruses and their host cells.